O anticomunismo em ação: a análise das perseguições políticas promovidas pelo Comando de Caça aos Comunistas (CCC) em Recife (1969): o atentado ao estudante Cândido Pinto, as ameaças a Dom Helder Câmara e o assassinato do Padre Henrique. - Pequeno, Mariana Cavalcanti (2023)
This research aims to analyze the historical and political context of the emergence of the far-right organization “Comando de Caça aos Comunistas” and its connection with the Military Dictatorship in the period of 1969 in the city of Recife. In this way, we seek to understand how the anti-communist discourse guided the political persecutions led by the murder of Father Henrique, the attempted murder of the student Cândido Pinto de Melo and the threats to Dom Helder Câmara. The methodology of this research has a bibliographic and documentary character, following a line of reasoning that takes us to the common thread between anti-communism and its combat through persecution, torture, deaths, bombings and disappearances, as a result of the actions carried out by this organization with the intention of annihilating any reaction expressed against the current order. As a result, mapping, critical analysis, and the effects of repressive practices of surveillance/social control are considered from the State Commission for Memory and Truth Dom Helder Câmara, based on critical 8 social theory, which helps us understand this historic clash between far-right organizations and active left-wing figures.